2013
DOI: 10.1071/an12192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding different levels of chromium-enriched live yeast in hairy lambs fed a corn-based diet: effects on growth performance, dietary energetics, carcass traits and visceral organ mass

Abstract: Forty Pelibuey × Kathdin lambs (35.5 ± 0.4 kg) were used in a 56-day feeding experiment to assess the effects of feeding different levels of chromium-enriched live yeast (Cr-YC) on growth performance, dietary energetics, carcass traits and visceral organ mass. The Cr-YC source contained 5.5 × 109 colony forming units (CFU) and 0.40 mg of Cr per gram. Treatments consisted of a dry rolled corn-based finishing diet supplemented with 0, 1, 2 or 3 g Cr-YC/lamb.day. Total daily dosages were: 5.5 × 109 CFU and 0.4 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
0
12
1
5
Order By: Relevance
“…There were no effects of treatments on HCW, dressing percentage and size measures of components of carcasses. Similarly, Estrada-Angulo et al (4) reported that daily supplementation up to 1.20 mg/head with Cr (from Cr-enriched yeast) did not affect (P ≥ 0.09) carcass length, carcass width, or leg length of lambs. In contrast to the present study, Estrada-Angulo et al (4) observed an overall positive effect of Cr supplementation on average daily gain and feed efficiency in lambs fed a corn-based diet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There were no effects of treatments on HCW, dressing percentage and size measures of components of carcasses. Similarly, Estrada-Angulo et al (4) reported that daily supplementation up to 1.20 mg/head with Cr (from Cr-enriched yeast) did not affect (P ≥ 0.09) carcass length, carcass width, or leg length of lambs. In contrast to the present study, Estrada-Angulo et al (4) observed an overall positive effect of Cr supplementation on average daily gain and feed efficiency in lambs fed a corn-based diet.…”
mentioning
confidence: 99%
“…In this sense, chromium (Cr) supplementation, as Cr propionate or Cr methionine, has shown increases in the percentage of carcass muscle and decreased carcass fat in pigs and poultries (1). In ruminants, Cr requirements have not been clearly established (2) and there is limited information available on the effects of Cr on carcass characteristics in feedlot cattle (3) and in feedlot lambs (4). In a recent study (5), linear decreases (P = 0.02) in kidney-pelvicheart fat and fat thickness were observed in finishing steers supplemented with chelated Cr (as Cr-enriched yeast) at daily levels of 0, 5, 10, or 15 mg/head.…”
mentioning
confidence: 99%
“…Ganancias diarias (rango de 0,230 a 0,291 kg/d), consumos de MS (rango de 0,230 a 0,291 kg/d) y eficiencias (rango de 0,180 a 0,210) similares a lo observado para el grupo control en este experimento se han informado para machos enteros cruzados de las razas Katahdin × Pelibuey consumiendo dietas de finalización libres de zeolita o de algún otro tipo de aditivo y con un contenido energético de 1,90 a 2,10 Mcal/kg de EN para mantenimiento (López-Carlos et al, 2011;Ríos et al, 2010Ríos et al, , 2014Estrada et al, 2013Estrada et al, , 2016. Por otra parte, la información sobre la respuesta productiva de borregos consumiendo dietas de finalización suplementadas con zeolitas es escasa.…”
Section: Resultados Y Discusiónunclassified
“…La eficiencia alimenticia se calculó dividiendo la GDP entre el promedio de consumo diario de MS. El consumo esperado de MS para cada uno de los tratamientos se estimó mediante las siguientes ecuaciones (NRC, 2007;Estrada et al, 2013 Donde los valores expresados en el numerador corresponden a los requerimientos de energía para mantenimiento y ganancia, y los valores expresados en el denominador representan la concentración energética de cada una de las dietas (tabla I). El coeficiente (0,276) se estimó para el peso adulto de 113 kg para corderos Kathadin × Pelibuey (NRC, 1985;Estrada-Angulo et al, 2013). La EN observada para las dietas se estimó por medio de la fórmula cuadrática: (ZinnyShen, 1998 (NRC, 1985;Estrada et al, 2013).…”
Section: Materiales Y Métodosunclassified
See 1 more Smart Citation